2015
DOI: 10.7860/jcdr/2015/12380.5850
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Burden of Depression During Pregnancy Among Pregnant Women Residing in Rural Setting of Chennai

Abstract: Introduction: Depression during perinatal period leads to adverse pregnancy outcome and of child growth. Our study aimed to examine the burden of antenatal depression and associated risk factors among pregnant women living in rural settings of Chennai, a southern state of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 22 publications
6
37
1
2
Order By: Relevance
“…The biologic plausibility for such a union is supported by various studies. 23,36,37 All these crosssectional studies emphasized towards the progressive association of psychosocial stress with periodontal diseases but, the multivariate analysis conducted in the present study (Table 4) revealed that stress has its utmost impact towards dental caries when compared with periodontal diseases and this is being considered to be the most important finding by the current study. The relationship between stress and dental caries has rarely been studied, maybe due to the fact that caries is considered as an infectious disease.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The biologic plausibility for such a union is supported by various studies. 23,36,37 All these crosssectional studies emphasized towards the progressive association of psychosocial stress with periodontal diseases but, the multivariate analysis conducted in the present study (Table 4) revealed that stress has its utmost impact towards dental caries when compared with periodontal diseases and this is being considered to be the most important finding by the current study. The relationship between stress and dental caries has rarely been studied, maybe due to the fact that caries is considered as an infectious disease.…”
Section: Discussionsupporting
confidence: 50%
“…18,23 Justification to these results could be that with the progression in pregnancy, physical changes associated with anxiety regarding labor and fetal outcomes or worries about changes in their personal life due to first pregnancy and child birth potentially worsen the stress response and lead pregnant women to have greater discomfort. Study by Marcus SM et al described that women who were unemployed were related to elevated symptoms of depression during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…As there is 45% increase in the antepartum depression (APD) recent past makes it a matter of great importance. 17 Risk factors attributable for the development of antenatal depression include young age, multiparity, place of residence, low income, lower educational attainment, history of depression, previous poor obstetrical outcome, previous history of depression, strained relationships with family members, type of family and support from family ,gender preference and pressure ,history of childhood sexual abuse, adverse events in the recent past and low social support. The prevalence of depression is to some extent higher in rural population compared to those in urban areas.…”
mentioning
confidence: 99%
“…Por otra parte, 10 de los estudios revisados por Biaggi et al (2016) indican que las mujeres con una edad considerada "más mayor" presentan asociaciones positivas con sus puntuaciones en depresión durante el embarazo (p.ej, Fisher et al, 2013;Weobong et al, 2014). Del mismo modo, hasta 10 estudios revisados (p.ej, Ratcliff, Sharapova, Suardi y Borel, 2015; Srinivasan et al, 2015) determinan que no existe asociación entre la edad de la mujer y los síntomas depresivos o la ansiedad durante el embarazo.…”
Section: Desempleounclassified
“…Biaggi et al (2016) refiere en sus conclusiones que también la falta de apoyo por parte de la pareja ha resultado ser un importante factor de riesgo para la depresión y la ansiedad prenatal. Del mismo modo, estos autores añaden que otros estudios Zeng, Cui y Li, 2015) muestran como la percepción del apoyo y la satisfacción con la propia pareja actúan como factores protectores frente a la depresión y ansiedad prenatal, mientras que los problemas o conflictos con la pareja o la insatisfacción o deterioro de la relación han sido identificados como factores destacados en el inicio de la ansiedad o depresión durante el embarazo (Giardinelli et al, 2012;Marchesi et al, 2009;Martini et al, 2015;Nasreen, Kabir, Forsell y Edhborg, 2011;Records y Rice, 2007;Srinivasan et al, 2015;Zelkowitz et al, 2004).…”
Section: Relación De Pareja Y Ajuste Maritalunclassified